Editorial: In this issue - Editors (Pécs journal of international and European law, 2025)
The editors are pleased to present issue 2024/II of the Pécs Journal of International and European Law, published by the Centre for European Research and Education of the Faculty of Law of the University of Pécs. In the Articles section, Dimitris Liakopoulos provides an analysis of how EU law perceives and regulates renewable energy and its environmental impact. Gergely Kappel presents a comprehensive literature review as regards the risks of artificial intelligence-based decision support in companies’ executive-level decision- making. In the Case Notes and Analysis section, Ágoston Mohay ponders the question whether the lengthy process of the EU’s accession to the ECHR is finally set to end thanks to the renegotiated draft accession agreement of 2023. In the Book Review section, firstly, Maria Melikidou reviews the monograph ‘The European Arrest Warrant and EU Citizenship. EU Citizenship in Relation to Foreseeability Problems in the Surrender Procedure’ by Joske Graat, published by Springer in 2022. Secondly, Tiwai Mhundwa looks at the edited volume ‘International Labour Mobility: How Remittances Shape the Labour Migration Model’ published by Palgrave Macmillan in 2023. A word of most sincere gratitude is due to the anonymous peer reviewers of the current issue. We encourage the reader to consider the PJIEL as a venue for your publications. With your contributions, PJIEL aims to remain a trustworthy and up-to-date journal of international and EU law issues.